A look behind the scenes: Experiences and reflections from my internship at Corpoturismo (2024)
My business profile internships were performed at the city's tourism board: Corporación Turismo Cartagena de Indias (CORPOTURISMO). Corpoturismo is a mixed and non-profit entity that works together with both the public and private sectors of Cartagena. Its main purpose is to articulate, plan and carry out actions and initiatives aimed at enhancing the competitiveness, quality and promotion of the wide tourism offer in the city, both nationally and internationally. All of this with the objective of generating sustainable value in the social, economic, environmental and cultural aspects of the city (La Corporación, s. f.). The corporation is additionally responsible for the administration of La Bodeguita tourist pier, located at downtown Cartagena, which is the main authorised departure point for boats heading to the Rosario Islands and other nearby tourist attractions, as well as the location of the entity's main offices. The Corporación turismo Cartagena de Indias has its own organisational structure headed by the board of directors, which is led by the Mayor together with members of the associations, the CEO, from which the different departments are derived: Gestion de la destination, Planification, Promotion and Marketing, Administrative and Finance, and lastly, a department in charge of the logistics and administrative work of La Bodeguita pier.